Precipitation Pathways: In Situ Liquid SAXS Studies on the Early Stage of Calcium Carbonate Formation (Part. Part. Syst. Charact. 6/2019). (14th June 2019) - Mohammed, Ahmed S. A.; Carino, Agnese; Testino, Andrea; Andalibi, Mohammad Reza; Cervellino, Antonio
Abstract : In article number1800482, Andrea Testino and co‐workers investigate calcium carbonate clusters in‐situ by small angle X‐ray scattering using a liquid jet setup at constant pH, temperature, and saturation level. The saturation is kept constant and below the critical condition for amorphous calcium carbonate formation. Data analysis allows for extracting information about entities in the liquid jet characterized by a higher density: highly hydrated small clusters (<2 nm) and large aggregates (superclusters, broad size distribution) are detected.